META ANALISIS: PENGARUH PENDEKATAN RME TERHADAP LITERASI MATEMATIS SISWA SMP DI INDONESIA - Suryani, Nur Syipa; Kamaliyah; Juhairiah (Uninus Journal of Mathematics Education and Science (UJMES), 2025)
A multitude of studies has been undertaken about the impact of the Realistic Mathematics Education (RME) approach on mathematical literacy at the junior high school level, although the results remain varied. This meta-analysis seeks to quantify the effect size of the RME technique on the mathematical literacy of junior high school pupils, taking into account the study characteristics, specifically grade level and sample size. The analysis encompassed 13 publications published between 2020 and 2024 that satisfied the inclusion and eligibility criteria. This study employed Comprehensive Meta Analysis (CMA) software, utilizing effect sizes computed via the Hedges-g equation grounded on the estimated random effects model. The analytical results indicated that the RME strategy significantly impacted the mathematical literacy of junior high school pupils, with an effect size of 1.385, categorized as very large. The implementation of RME substantially enhances pupils' mathematical literacy. The RME technique is most effective at grade VIII and is preferably utilized with a large sample size.